Do conceito de Deus do período pré-crítico ao crítico pela elucidação do princípio da ilusão transcendental em Kant - Tietz, Suzana Talita (2023)
Immanuel Kant's Critique of Pure Reason brought a new treatment of reason and the theory of knowledge, focused on the question of the limits of knowledge from the point of view of the human faculty of thinking. In contrast to the traditions of empiricism/skepticism and rationalism, the proposal of the Transcendental Philosophy expresses as novelty its occupation, less of objects than of the human way of knowing. By emphasizing there the active and spontaneous character of the act of knowing, Kant presupposed and founded the possibility of anticipating the a priori elements or structures of the subject (the faculties) to deal with the objects of knowledge as with those of thought. While in the Transcendental Analytics he exposed the elements aimed at the constitutive character of knowledge, in the Transcendental Dialectics he exposed the mode of operation of reason that, although it does not constitute knowledge of nature, is relevant to the whole of this pure faculty. Belonging to this mode of operating with concepts that have only transcendental significance, since they lack empirical reality, belongs the domain of those concepts that represent the continuation of the activity of reason (Vernunft) outside the knowledge of the understanding (Verstand), but not detached from it. These concepts are those of God, soul, and freedom, which are connected with the sources of ancient metaphysics (theology, cosmology, and psychology). In the thematization of the concept of God we present its unfolding from pre-critical to critical thought in Kant. If in the first texts on the subject Kant tried to elucidate the dogmatic and arbitrary elements in the use of this concept, in the following ones he expresses his own (transcendental) way of extracting from the necessity of this concept by reason the systematic character of an ideal of rational thought, which could not be missing in thought, namely, the concept of totality. Here knowledge proceeds by means of reasoning (inference). Linked to this way of proceeding Kant discusses in the text of the Critique the three types of proof for the existence of God, corresponding to attempts to pass an object of mere thinking as an object of determined knowledge. In essence, such an attempt reveals a commonplace operation of self-deception that afflicts reason, in which it believes it is dealing with a matter supplied by sensibility, when it deals only with laws of its own reason to think an object (totality) according to its reflective need. As mere appearance (Schein) of knowledge, in contrast, it is about exposing the legitimacy status of ideas as concepts that have no sensible reference, in order to extract from them the means to guard against becoming entangled in a transcendental illusion. The Transcendental Dialectic then aims at instructing and disciplining reason not to be deceived by a mere concept, for through thought it aims at a systematic completeness. If this is not the object of knowledge, then it is the task of criticism to evaluate the legitimacy of ideas and, for us, the organizing function of the idea of God which, transcendent to knowledge, receives by the critical approach to reason an internal coherence indispensable to thinking.